Fracture Behavior of RT-PMMA Under Impact Loading - Mat Jali, Norazrina; Longere, Patrice (International Journal of Integrated Engineering, 2020)
Fracture mechanism of polymer under high strain rate loading is still today a complicated issue in developing their design as protection structure. In this paper, we aim to investigate the crack arrest capability of RT-PMMA when subjected to impact loading. For that purpose, Kalthoff and Winkler (KW)-like impact tests are performed using the STIMPACT platform gas launchers. Double notched specimens were impacted on the edge within a range of impact velocities (50-140 m/s). During the investigation, the failure mechanism is recorded by a high speed camera. The stress whitening phenomena is explained and it is shown that addition of rubber to PMMA matrix aids to enhance its impact toughness. This involves energy dissipation by the rubber and higher energy required for crack propagation in rubber toughened RT-PMMA as compared in neat PMMA. High impact velocities promote greater effect proved by large number of fragments produced aftermath. By carrying out uniaxial tensile tests, it was established that the mechanical behaviour of RT-PMMA strongly depends on strain rate and temperature.